2017
DOI: 10.1155/2017/6935402
|View full text |Cite
|
Sign up to set email alerts
|

Glycomacropeptide Attenuates Inflammation, Pruritus, and Th2 Response Associated with Atopic Dermatitis Induced by 2,4-Dinitrochlorobenzene in Rat

Abstract: Atopic dermatitis (AD) is one of the most common skin diseases, whose incidence is increasing in industrialized countries. The epicutaneous application of a hapten, such as 2,4-dinitrochlorobenzene (DNCB), evokes an experimental murine AD-like reaction. Glycomacropeptide (GMP) is a dairy bioactive peptide derived from hydrolysis of κ-casein by chymosin action. It has anti-inflammatory, prebiotic, and immunomodulatory effects. The present study was aimed to investigate the effect of GMP administration on DNCB-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 54 publications
4
24
0
Order By: Relevance
“…It is reported that over expression of Th2 cytokines, including IL-4, IL-5, and IL-10, are predominant in the acute phase of AD lesions, which stimulate the high production of IgE [45]. Meanwhile, Th1 producing IFN-γ and other proinflammatory cytokines, such as IL-6 and TNF-α, were abundant in the chronic phase of AD [46].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that over expression of Th2 cytokines, including IL-4, IL-5, and IL-10, are predominant in the acute phase of AD lesions, which stimulate the high production of IgE [45]. Meanwhile, Th1 producing IFN-γ and other proinflammatory cytokines, such as IL-6 and TNF-α, were abundant in the chronic phase of AD [46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GMP intake also reduces the proliferative response of splenocytes induced by mitogens in the rat [ 28 ]; a widely validated property of GMP by in vitro assays [ 29 , 30 , 31 ]. When GMP is orally and prophylactically administered to rats, it reduces the type 2 inflammatory response and prevents lung and skin damage in experimental models of asthma and atopic dermatitis [ 32 , 33 ]. In both studies, GMP increases IL-10 expression on affected tissues.…”
Section: Introductionmentioning
confidence: 99%
“…GMP also inhibited eosinophils infiltration, goblet cells hyperplasia, and collagen deposit in lung tissue [59]. Equivalent results were obtained in allergen-induced atopic dermatitis model, where GMP reduced the intensity of cutaneous inflammatory process and edema, abolished pruritus, and reduced eosinophils recruitment and mast cells hyperplasia in dermis [60]. In both models, expression of IL-5 and IL-13 was markedly inhibited in lung and skin, while expression of IL-10 was increased.…”
Section: The Immunomodulatory Properties Of Gmpmentioning
confidence: 85%
“…In recent years, a Mexican laboratory led by Salinas [55,[59][60][61] has focused on the study of the immunomodulatory activity of GMP in experimental allergy models. They found that oral administration of GMP to rats before and during sensitization with allergen significantly reduces the level of allergen-specific IgE in serum, and also decreases the proliferative response and the production of IL-13 by splenocytes stimulated by the allergen [55].…”
Section: The Immunomodulatory Properties Of Gmpmentioning
confidence: 99%